Examinations of Errors in a D/Pd Gas-loading System when Using a Heat-flow Calorimeter. Issue 1 (August 2021) - Wang, Xingye; Shen, Bingjun; Jin, Lihong; Zhou, Dan; Tian, Jian
Abstract: Measurement of a reaction between deuterium (hydrogen) gas and materials using a calorimeter which is calibrated by nitrogen will show erroneous excess heat power production due to the structure of the reaction chamber and the difference of thermal conductivity of the gases used in the calibration and triggering experiments, which leads to the energy generated in the chamber of the calorimeter has not been totally measured. The error is not obvious at low applied power, and it increases significantly with the increase of applied power. This insidious error is discussed by using a stable heat-flow (Seebeck) calorimeter and procedures to reduce error are put forward. And the authenticity of Rossi's patent is questioned.